Knowledge of oral health related to dental caries and its relationship with the father-child dyad in Cartagena, Colombia - Díaz-Cárdenas, Shyrley; Perez-Puello, Sthefanie del Carmen; Tirado-Amador, Lesbia Rosa (Universidad y Salud, 2024)
Introduction: Currently, some men take care of their children in single-parent families. Therefore, it is important for them to know the factors that could affect the oral health (OH) of their children. Objective: To estimate the association between knowledge of OH and presence of dental caries (DC) and its relationship with the father-child dyad. Materials and methods: Analytical cross-sectional study conducted on a black population (153 dyads) in 2017. A self-administered questionnaire was applied to father to assess: sociodemographic variables, OH’s knowledge and self-perception, and child habits. Fathers and children were surveyed about presence and experience regarding DC. Finally, association estimation and nominal logistic regression were carried out. Results: The prevalence of DC was 60.1% and 98% in children and fathers, respectively. The multivariate model showed an association between OH insufficient knowledge, presence and experience of DC, inadequate oral hygiene habits of the child, unsupervised oral tooth brushing, working fathers, low income, and Catholic religion. Conclusion: The prevalence of dental caries in children is associated with inadequate knowledge in oral health and low income of working fathers. These factors should be taken into account in oral health educational programs.